Declining Organizational Size and Increasing Unemployment Rates: Predicting Employee Absenteeism from Within- And Between-Plant Perspectives - Markham, Steven E.; McKee, Gail H. (Academy of Management Journal, 1991)
The impact of increasing unemployment rates and decreasing organizational size on absenteeism was assessed for pooled monthly data from 17 plants over a five-year period. As the organizations became smaller and as local unemployment rates increased, absence rates decreased. Employees also appeared to anticipate economic downturns by decreasing absenteeism in the month prior to changes in unemployment rates.